Efforts to Improve BIPA Students' Reading Skills Through the Utilization of Concept Map-Based Teaching Materials Containing the Legend of Surabaya - Sa'adah, Widadatus; Anas Ahmadi, Anas; Raharjo, Resdianto Permata (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2024)
AbstractTeaching materials are an important component to influence the motivation and interest of BIPA learners. This study aims to describe the use of teaching materials based on concept maps containing the legend of Surabaya based on the results of problem analysis and needs analysis. Data collection techniques were carried out through literature studies, observations, and interviews with teachers, students, and the head of BIPA, Surabaya State University. The data analysis technique used the Miles Huberman model. The results of the study showed that teachers agreed to the use of teaching materials based on concept maps. Concept maps are recognized as an effective graphic tool in language learning. Utilization of concept maps using Canva. BIPA students responded positively to the use of concept maps using Canva media. The legend of Surabaya was chosen as the content of teaching materials because the history of Surabaya is important to be used as a topic for developing teaching materials as a means of promoting the city of Surabaya and Surabaya State University itself. The use of teaching materials based on concept maps with the content of the Surabaya legend will be applied to level 3 reading classes at Surabaya State University.